The Role of Sustainability Risk in the Relationship Between Profitability and Firm Value in Indonesia - Meiny Grace Porajouw; James Leri S; Billy Ivan Tansuria (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: The study aims to determine whether, for IDX-listed companies, sustainability risk mitigates the correlation between profitability and firm value. Research Method: The following metrics are used to assess the worth of a company: Tobin's Q for profitability, ESG Risk Ratings for sustainability risk, and imbalanced panel data from 84 businesses spanning 2022–2024 (140 firm-year observations). Controlling for business size, age, leverage, and liquidity, the research employs REM GLS with robust standard errors and moderated regression. Results and Discussion: Profitability is positively related to firm value. The profitability–sustainability interaction is negative but not statistically strong in the linear model, indicating limited evidence of moderation. However, simple slopes analysis showed that the effect of profitability on firm value declines as sustainability risk increases, suggesting a conditional pattern rather than a direct moderating effect. Implications: Sustainability risk may influence how the market interprets profitability signals. Managers should manage sustainability risk to maintain valuation credibility, while investors may consider it contextual information when evaluating performance. Originality: This study provides an early exploration from Indonesia that sustainability risk acts as a contextual factor that conditions, rather than directly determines, the profitability–firm value relationship.